The Promise and Perils of Crowdfunding: Between Corporate Finance and Consumer Contracts. Issue 1 (11th January 2018) - Armour, John; Enriques, Luca
Abstract: 'Crowdfunding' is a burgeoning phenomenon. Its still‐evolving status is reflected in diversity of contracting practices: for example, 'equity' crowdfunders invest in shares, whereas 'reward' crowdfunders get advance units of product. These practices occupy a hinterland between existing regimes of securities law and consumer contract law. Consumer protection law in the UK (but not the US) imposes mandatory terms that impede risk‐sharing in reward crowdfunding, whereas US (but not UK) securities law mandates expensive disclosures that hinder equity crowdfunding. This article suggests that while crowdfunding poses real risks for funders, the classical regulatory techniques of securities and consumer law provide an ineffective response. Yet, a review of rapidly‐developing market mechanisms suggests they may provide meaningful protection for funders. An initially permissive regulatory approach, open to learning from market developments yet with a credible threat of intervention should markets fail to protect consumers, is justified.